Macrocalcification in thyroid nodule - Verma, Naina; Mohindroo, Shobha; Azad, Ramesh; Mohindroo, N. K. (International Journal of Research in Medical Sciences, 2017)
Background: The thyroid is one of the largest endocrine organs. The prevalence of palpable thyroid nodules increases with age and is 4-7% in a middle-aged population. Objective of present study was to understand if thyroid malignancy is associated with macrocalcification. Methods: 34 cases were with thyroid nodules were evaluated initially with sonography and then with FNAC, the results of which were given on the basis of Bethesda system. Results: On USG, 23 (67.6%) nodules had macrocalcifications, 5 (14.7%) had microcalcifications and 6 (17.6%) had both micro as well as macrocalcifications. Cytology of 23 nodules with macrocalcification were non-diagnostic in 8.7%, benign 73.9%, suspicious for malignancy in 8.7 % and malignant in 8.7%. Only 2 lesions with macrocalcification and 1 with both macro and microcalcification came out to be non-diagnostic. 17 lesions with macrocalification were diagnosed as benign, 2 as suspicious for malignancy and 2 as malignant. While 3 lesions with microcalcification were diagnosed as malignant on FNAC and 2 as benign. Conclusions: Macrocalcification is not a good indicator for malignancy.